In reference to fiction autobiography genre in the German studies in the German study of Literature (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article is devoted to the studying of the literary autobiography genre specification question in the German literary studies of the XX century. Separate literary autobiography scientific researches problems of the German scholars are analyzed in the article. In the center of the stated period, there is the autobiography narration truthfulness question and memory role when being created, autobiography genre separation from the other genres, autobiography creation motivation and the narrative perspective change, the women autobiography peculiarities. The W. Dilthey philosophy literary autobiography treatment is analyzed.
Keywords: autobiography; author; genre; individuality; self-depiction; memory